Experimental assessment of a full scale prototype thermal energy storage tank using paraffin for space heating application. (February 2020) - Koukou, Maria K.; Dogkas, George; Vrachopoulos, Michail Gr.; Konstantaras, John; Pagkalos, Christos; Stathopoulos, Vassilis N.; Pandis, Pavlos K.; Lymperis, Kostas; Coelho, Luis; Rebola, Amandio
Abstract: In this work, a full scale prototype latent heat thermal energy storage unit has been designed, constructed, and experimentally analysed for its performance considering heating application conditions and two energy sources, solar and geothermal energy. It comprises a rectangular tank filled with phase change material and a finned tube staggered heat exchanger. Water is used as heat transfer fluid. To study its performance, selected heat transfer fluid inlet temperatures and flow rates were applied and two commercial organic phase change materials were tested, A44 and A46. Heat transfer fluid outlet temperature, heat transfer rate and stored energy were evaluated as a function of the conditions studied. Based on the results, it is concluded that A44 is more efficient during the charging period, taking into account the two energy sources, solar and heat pump. The water outlet temperature has a more stable evolution when using A44 instead of A46 and the heat transfer rate is higher too. A44 also exhibits higher storage capacity than A46 during the discharging process and more stable heat transfer rate for both flow rates The developed methodology can be applied to study different PCMs and building